2018
DOI: 10.1007/s00128-018-2345-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heavy Metal Pollution on Ammonia Oxidizers in Soils in the Vicinity of a Tailings Dam, Baotou, China

Abstract: Soil heavy metal pollution has received increasing attention due to their toxicity to soil microorganisms. We have analyzed the effects of heavy metal pollution on ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) in soils in the vicinity of a tailings dam of Baotou region, China. Results showed that AOB were dominated with Nitrosomonas-like clusters, while AOA was dominated by group1.1b (Nitrososphaera cluster). Single Cd and Cr contents, as well as compound heavy metal pollution levels, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…It can, therefore, be adduced that members of Thaumarchaeota were sensitive to HMs and chemicals contained in the TWW that were consistently released into L2. This observation agrees with the conclusions of Liu et al (2018) and Guo et al (2019) but negates the suggestion of He and colleagues (2018) that there may be HM-resistant Thaumarchaeota organisms in metal polluted freshwater. In agreement with the findings of Guo and colleagues (2019), Bathyarchaeota remained abundant in both pristine L1 and TWW-impacted L2, only that the relative abundance became reduced in the TWW-impacted L2 ecosystem, possibly due to the toxic HMs/metalloids in the TWW, and some members might exhibit resistance to HMs/ metalloids.…”
Section: Discussionsupporting
confidence: 90%
“…It can, therefore, be adduced that members of Thaumarchaeota were sensitive to HMs and chemicals contained in the TWW that were consistently released into L2. This observation agrees with the conclusions of Liu et al (2018) and Guo et al (2019) but negates the suggestion of He and colleagues (2018) that there may be HM-resistant Thaumarchaeota organisms in metal polluted freshwater. In agreement with the findings of Guo and colleagues (2019), Bathyarchaeota remained abundant in both pristine L1 and TWW-impacted L2, only that the relative abundance became reduced in the TWW-impacted L2 ecosystem, possibly due to the toxic HMs/metalloids in the TWW, and some members might exhibit resistance to HMs/ metalloids.…”
Section: Discussionsupporting
confidence: 90%
“…The majority (98.77%) of AOA sequences are affiliated to Group I.1b, with high homology to arable soils [31] and coastal alkaline soils [32]. Nitrososphaera were the major AOA populations, as OTU39 was high homology with Nitrososphaera viennensis [33], OTU10 was high homology with Nitrososphaera gargensis [34], and OTU38 and OTU42 were high homologies with Candidatus Nitrososphaera [35]. The phylogenetic tree (Figure 5) showed that AOB OTUs were divided into seven clusters: Cluster 4, Cluster 1, Cluster 3a, Cluster 3a.1, Cluster 3a.2, and Cluster 3b belong to the Nitrosospira group of the phylum β ‐Amastigotes, and Cluster 7 belongs to the Nitrosomonas group of the phylum β ‐Amastigotes.…”
Section: Resultsmentioning
confidence: 99%
“…This AOB increase might be due to the introduction of exogenous microbial agents, increasing soil mineralization. The active carbon and nitrogen improved by mineralization can promote amoA AOB growth ( Liu et al, 2018 ), whereas amoA AOA plays a role in the soil environment with low nitrogen content. Also, more bacterial activity was found in low contaminated soil than with high contamination because of the growth restrictions by high Cd concentration manifesting as the inhibition of cell growth and cell detoxification mechanism (i.e., intracellular efflux of Cd +2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This AOB increase might be due to the introduction of exogenous microbial agents, increasing soil mineralization. The active carbon and nitrogen improved by mineralization can promote amoA AOB growth (Liu et al, 2018), whereas amoA AOA plays a role in the soil environment with low nitrogen content. Also, more bacterial activity was found in low contaminated soil than with high 10.3389/fpls.2022.913787…”
Section: Effect Of the Different Supplemented Strains On Soil Functio...mentioning
confidence: 99%
See 1 more Smart Citation